EFEKTIVITAS PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT JAM EPOXY PADA SISWA DISABILITAS RUNGU - Suci Amelia Cahyati; Setia Budi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was driven by the tendency of students with hearing impairments to improve their skills in creating epoxy clocks. These students possess artistic talent in painting that can be further developed through three-dimensional media such as epoxy-based clocks. Therefore, the researcher sought to implement the project-based learning method to enhance these students’ painting skills. The aim of this study is to determine the effectiveness of the project-based learning method in improving the skills of making epoxy clocks among students with hearing impairments at SLB Negeri 1 Pariaman. This research adopts a quantitative approach using an experimental method known as single subject research (SSR) with an A-B design. Data were collected through observation using instruments and documentation in May 2025 with one subject. Data analysis was carried out using the visual graph method. The results revealed that the skills of making epoxy clocks among students with hearing impairments improved following the intervention with the project-based learning method, as indicated by an increase in skill frequency both within and across conditions.